The Flowering Plants : Flowering Rush to Rushes: Flowering Rush to Rushes. (Southern Illinois University Press, 2006)
The second edition of Flowering Plants: Flowering Rush to Rushes offers new material, including a preface, seventeen new illustrations of the additional species now known from Illinois, a revised list of illustrations, and an appendix of the additions and changes since 1970 in the identification, classification, and location of the plants included in the first edition. This new edition of the first volume in the multi-volume series of The Illustrated Flora of Illinois-which provides a working reference for the identification and classification of these plant forms in the st.